Impact of human papillomavirus on outcome in patients with oropharyngeal cancer treated with primary surgery. Issue 10 (10th July 2017) - Broglie, Martina A.; Stoeckli, Sandro J.; Sauter, Rafael; Pasche, Philippe; Reinhard, Antoine; de Leval, Laurence; Huber, Gerhard F.; Pezier, Thomas F.; Soltermann, Alex; Giger, Roland; Arnold, Andreas; Dettmer, Matthias; et al.
Abstract: Background: Knowledge about prognostic factors in surgically treated patients with oropharyngeal squamous cell carcinoma (SCC) is limited. The purpose of this study was to identify influential factors on survival in a large cohort of patients with surgically treated oropharyngeal SCC. Methods: Retrospective analysis of survival estimates in patients with surgically treated oropharyngeal SCC using tumoral positivity for human papillomavirus (HPV) and risk‐of‐death categories according to a study from 2010 as stratification factors. Results: The 5‐year overall survival (OS) and disease‐specific survival (DSS) rates after surgery alone were higher in HPV‐associated oropharyngeal SCC (OS 80% vs 62%; P = .01; DSS 92% vs 76%; P = .03). Patients in the low‐risk category had higher survival rates (OS 91%; DSS 99%) than patients in the intermediate‐risk group (OS 63%; DSS 83%), and high‐risk group (OS 61%; DSS 75%). Conclusion: Nonsmokers with HPV‐positive oropharyngeal SCC have a better prognosis than smokers with HPV‐positive oropharyngeal SCC and also than patients with HPV‐negative tumors when treated by surgery alone.